PEMODELAN TRANSIEN ELEKTROMAGNETIK SUB SISTEM GITET NEW AUR DURI - Vevel, Ofpria; Amin, Rahmat Rachim; Yamashika, Herris; Dwiharzandis, Aggrivina; Lovita, Wiwin (Rang Teknik Journal, 2026)
Electromagnetic transient modeling is an analytical method used to understand the transition phenomena that occur in electric power systems due to disturbances, such as short circuits, switching, and lightning. This study aims to conduct electromagnetic transient modeling on the GITET New Aur Duri subsystem to determine the characteristics of the system's response to transient conditions. The method used is system modeling using electric power system simulation software by entering network component parameters such as transmission lines, transformers, and voltage sources. The simulation results show that transient phenomena can cause rapid changes in voltage and current in a very short time. Therefore, this modeling is important to help analyze and understand system behavior so that it can improve the reliability and safety of electric power system operations on the GITET New Aur Duri subsystem.Keywords: electromagnetic transients, EMTP/ transient simulation, electric power systems, GITET New Aur Duri, power system disturbances, system modeling.